Enhanced Performance of Perovskite Solar Cell via Controlling Layer Thickness - Ho, Phuong (Journal of Technical Education Science, 2023)
In this study, Perovskite material methylammonium lead iodide (CH3NH3PbI3) was successfully fabricated using a two-step sequential solution deposition method. The precursor solution of lead iodide was first spin-coated, followed by immersing the film into a solution of CH3NH3I to form the Perovskite layer. The Perovskite material was then successfully applied as a light-harvesting material in Perovskite solar cells. The power conversion efficiency of the devices was optimized by varying TiO2 blocking layer, TiO2 mesoporous layer, and perovskite capping layer thickness. The best Perovskite solar cell exhibits a power conversion efficiency of 7.72% with a short-circuit photocurrent density JSC of 17.26 mA/cm2, an open-circuit photovoltage VOC of 0.94 V, and a fill factor of 47.6%; with the thicknesses of TiO2 blocking layer, TiO2 mesoporous layer, and perovskite capping layer of 100 nm, 200 nm, and 400 nm, respectively. The results show that Perovskite material has potential for solar cell application.